Modernism and Postmodernism: A Study of the Islamic Teachings with Special Reference to the Related Issues of Pakistani Society - Muhaimin, Abdul (Journal of Islamic and Religious Studies, 2017)
This study elaborates the difference and connection between modernism and postmodernism eras while highlighting their backgrounds. The research highlights the teachings of Islam in terms of modernism and postmodernism. The research brings to light the influence of modernism and postmodernism on Muslim societies. What are the far reaching impacts of the modernism and postmodernism eras of Muslim societies and how well a common Muslim is equipped to address the issues related to postmodernism. The study primarily focuses on the related issues in Pakistani society and explains the role and the influence of religious scholars of their understanding of the terms modernism and postmodernism. The study focuses on the awareness of the ’Ulamā in addressing these global challenges and subsequently the future of Pakistani society. The study has an element of quantitative research and it indicates towards the on ground realities on the issue with the help of a latest survey on modernism and postmodernism.